Ecological niche models of invasive seaweeds. Issue 4 (23rd July 2015) - Marcelino, Vanessa R.; Verbruggen, Heroen; Graham, M.
<x xml:space="preserve">Abstract</x> Ecological niche models (ENMs) are commonly used to calculate habitat suitability from species' occurrence and macroecological data. In invasive species biology, ENMs can be applied to anticipate whether invasive species are likely to establish in an area, to identify critical routes and arrival points, to build risk maps and to predict the extent of potential spread following an introduction. Most studies using ENMs focus on terrestrial organisms and applications in the marine realm are still relatively rare. Here, we review some common methods to build ENMs and their application in seaweed invasion biology. We summarize methods and concepts involved in the development of niche models, show examples of how they have been applied in studies on algae and discuss the application of ENMs in invasive algae research and to predict effects of climate change on seaweed distributions.